From higher aims to hired hands : the social transformation of American business schools and the unfulfilled promise of management as a profession - Khurana, Rakesh, 1967- (Princeton University Press, 2007)
"Is management a profession? Should it be? Can it be? This major work of social and intellectual history reveals how such questions have driven business education and shaped American management and society for more than a century. The book is also a call for reform. Rakesh Khurana shows that university-based business schools were founded to train a professional class of managers in the mold of doctors and lawyers but have effectively retreated from that goal, leaving a gaping moral hole at the center of business education and perhaps in management itself. Khurana begins in the late nineteenth century, when members of an emerging managerial elite, seeking social status to match the wealth and power they had accrued, began working with major universities to establish graduate business education programs paralleling those for medicine and law. Constituting business as a profession, however, required codifying the knowledge relevant for practitioners and developing enforceable standards of conduct. Khurana, drawing on a rich set of archival material from business schools, foundations, and academic associations, traces how business educators confronted these challenges with varying strategies during the Progressive era and the Depression, the postwar boom years, and recent decades of freewheeling capitalism."--Jacket